2006
DOI: 10.1128/iai.00781-06
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phase- and Nutrient Limitation-Associated Transcript Abundance Regulation inBordetella pertussis

Abstract: To survive in a host environment, microbial pathogens must sense local conditions, including nutrient availability, and adjust their growth state and virulence functions accordingly. No comprehensive investigation of growth phase-related gene regulation in Bordetella pertussis has been reported previously. We characterized changes in genome-wide transcript abundance of B. pertussis as a function of growth phase and availability of glutamate, a key nutrient for this organism. Using a Bordetella DNA microarray, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 45 publications
6
43
3
3
Order By: Relevance
“…The effect of glutamate limitation on gene expression in B. pertussis first was investigated by DNA microarray analysis (34). Contrary to the case in the present study, the amount of T3SS transcripts was decreased under glutamate limitation.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The effect of glutamate limitation on gene expression in B. pertussis first was investigated by DNA microarray analysis (34). Contrary to the case in the present study, the amount of T3SS transcripts was decreased under glutamate limitation.…”
Section: Discussioncontrasting
confidence: 52%
“…Contrary to the case in the present study, the amount of T3SS transcripts was decreased under glutamate limitation. Moreover, decreased transcript levels were observed during the transition from exponential to stationary phase (34). It is notable that Nicholson et al demonstrated that B. bronchiseptica expressed higher levels of T3SS genes and cytotoxicity mediated by T3SS in late exponential phase and stationary phase than during mid-exponential phase (35).…”
Section: Discussionmentioning
confidence: 97%
“…For example, the expression of numerous pathogenic genes including SPI-1 in Salmonella enterica serovar Typhimurium is activated by an ArcAB-TolC efflux pump (63), and the transcription of T3SS in Pseudomonas aeruginosa is inhibited by the magnesium transporter MgtE (1). It is also known that the influx of environmental small molecules is linked to bacterial pathogenesis; the internalization of N. gonorrhoeae into human cells is inhibited by the influx of phosphate via the gonococcal major outer membrane porin PorB of serotype A (P.IA) (22,55), and transcript levels of many virulence genes in Bordetella pertussis are reduced under L-gluta- ϩ -gltM ϩ strain(HT1125), ⌬gltT-⌬gltM mutant (HT1414), the ⌬gltT-⌬gltM mutant in which gltT ϩ -gltM ϩ genes were ectopically complemented (HT1428), the gltT(Am) mutant (HT1452), the gltM(Oc) mutant (HT1453), and the derivatives of additional complementation of the popc-gltM ϩ gene at the iga locus of the above mutants (HT1539, HT1533, and HT1538) ( mate-depleted conditions (29). The transcription of T3SS in P. aeruginosa is also induced under a low-Ca 2ϩ environment by the elevation of cyclic AMP (cAMP), which induces transcription in cooperation with Vfr, a functional homologue of the E. coli cAMP receptor protein (64).…”
Section: Vol 79 2011 L-glutamate Influx Enhances the Meningococcal mentioning
confidence: 99%
“…In the laboratory, the bacteria shift to the avirulent Bvg Ϫ phase in response to the perception by BvgS of modulators such as MgSO 4 or nicotinate, at low temperatures, or under conditions of nutrient restriction (9)(10)(11)(12). We have shown, using a Phos-tag assay, that addition of nicotinate to the bacteria causes the dephosphorylation of BvgA much faster than if the reaction occurs spontaneously (12).…”
mentioning
confidence: 99%